Synchrotron Radiation Application for Lattice Strain Measurements - Gadalińska Elżbieta; Baczmański Andrzej; Sołoducha Kamil (Fatigue of Aircraft Structures, 2014)
The methods most commonly used for the determination of the elastic lattice deformation and distortion are diffraction methods, which enable to perform measurements of stresses and elastic properties of polycrystalline materials. The main advantages of diffraction methods are associated with their non-destructive character and the possibility to be used for macrostress and microstress analysis of multiphase and anisotropic materials. Diffraction methods enable taking measurements selectively only for a chosen alloy phase. This is very convenient when several phases are present in the sample since measurements of separate diffraction peaks allow the behaviour of each phase to be investigated independently.